Karate Self-Defense as an Effort to Develop Life Skills for Teenage Karate Practitioners A Narrative Study - Sartono Tono; Oman Hadiana (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
Karate is a martial art from Japan. Karate should not only focus on physical abilities and techniques. It also plays an important role in developing authentic life skills, especially for young karate practitioners. Objectives: The objective of this study is to explore how karate as a martial art can be used as a means of developing life skills for young karate practitioners. Methods: The research method used is a narrative literature review, which aims to provide information and knowledge through the analysis of previously published literature. The participants are documents in the form of relevant articles from 2021 to 2025, with criteria including being written in Indonesian and English. The data analysis technique used is thematic narrative analysis. Results: Ten relevant articles were identified as research findings. Specifically, the results indicate that structured and programmed karate training can optimize interpersonal and intrapersonal life skills such as motivation, respect, cooperation, sportsmanship, discipline, responsibility, and empathy. These skills are closely aligned with the values of bushido in karate. However, there are challenges in internalizing such character traits, including the perception that karate is associated with violent activities, varying quality of instructors, and competitive pressure that causes anxiety. Conclusion: It is concluded that karate is an effective medium for developing character values and life skills for young karateka, but this requires a holistic and comprehensive approach.